Memorial to the Minister of Health - Loat, Lily (London : National Anti-Vaccination League)
1928-11-30 1928 1920s 8 pages world, and has extended over such a long period of time, that in spite of hostile criticism it has been accepted as a fact in all civilised countries.” An exactly similar paragraph could have been written 130 years ago in defence of the former practice of smallpox inoculation which is now a penal offence! The Committee also comment on the mild character of the smallpox which has been prevalent in this country during recent years, and draw special attention to the statistical absence of vaccinated cases under 12 to 13 years of age. They add, however, “that to maintain the immunity of a population at a satisfactory level re-vaccination must be carried out from time to time. We are confident that vaccination and revaccination systematically and efficiently carried out would eradicate smallpox and would render negligible the risk of the disease gaining any footing in the future. We know of no action, other than this, which would secure for the individual and for society effective protection against smallpox.” And yet it can be shown (see figures below) that nations possessing all the protection here desiderated are far worse off than England without it! They quote certain figures (taken at random) in regard to the vaccination statistics in certain counties, etc., in this country. They also comment on the enormous neglect of vaccination in some counties such as Leicestershire, Bedfordshire and Gloucestershire. In view of the dogmatic claims which they make in regard to the protective powers of vaccination, it is strange that they did not also compare the smallpox experience of these ill-vaccinated counties with that of the well-vaccinated. And yet it is not strange. The comparison would have completely destroyed the dogma they enunciate. Nor is this the only instance in which they display a like economy in the production of figures. They admit that the statements they have put on record are the ones which they consider relevant to a discussion of the matter. It is now more than 30 years since the Royal Commission issued their voluminous Report on the whole subject, and one would naturally have thought that the Rolleston Committee would have had something special to say about the smallpox experience of this country during that period, particularly in view of the fact that in the meantime a large diminution had taken place in the number of vaccinations performed, in consequence of the enactment of the Conscience Clause of 1907. You will remember that when the first Conscience Clause was passed in 1898 it was enacted that it should run for 5 years only, that period being-apparently considered sufficient to decide the extent of the untoward results which the Parliament of that day felt sure would follow such a “tremendous experiment.” (Lord Lister.) Six times five years have now elapsed and what has happened? The Rolleston Committee apparently do not consider it relevant to the discussion to point out that during that period two records have been established in this country: (1) fewer vaccinations have been performed than in any similar period in the history of the practice and (2) fewer smallpox deaths have occurred than in any other similar period since vaccination was introduced. In fact for many years past smallpox has been a less fatal disease than chickenpox ! These two records are succinctly displayed in the following table :— Period. Average annual per cent. of births vaccinated. Average annual Smallpox mortality. Per cent. of deaths from Smallpox under 5 to deaths from Smallpox at all ages. Per million living. At all ages. Per million living. Under 5. 1871—1880 85.6 228 518 30.2 1881—1890 83.3 45 80 22.9 1891—1900 68.5 14 29 26.3 1901—1910 69.6 13 22 19.6 1911—1920 44.1 0.4 0.6 15.1 1921—1925 (5 years) 42.7 0.3 0.7 22.6 Why were these figures, or similar figures, not quoted in the Rolleston Report? 6 292/840/1/13